COVID-19 infection and vaccine status in patients with chronic kidney diseases - Haider, M. Shafiul; Arjumand, Marina; Mahtab Ul Islam, Syed; Abdul Aziz, N. M.; Mahmud, M. Hasan (International Journal of Research in Medical Sciences, 2023)
Background: The COVID-19 virus has had a great effect globally, changing many commonalities. The incidence of COVID-19 had weakened the immune system, leading to more severe outcomes of various common diseases. Since its early development, the vaccination of COVID-19 has also had mixed responses. The aim of the study was to observe the incidence rate of COVID-19 infection and vaccination status among chronic kidney disease patients. Methods: In this study 50 (27 male and 23 female) adult skulls were investigated to determine the type of asterion, its distance from important bony landmarks and also the nearby venous sinuses were measured. Results: Majority (41.61%) of the participants had been between the ages of 41-55 years old, and 64.84% male prevalence was observed. 60.65% of the participants had been from rural areas. A large portion of the participants (38.06%) did not have any comorbidities, while multiple comorbidities were present among many of the remaining participants. Hypertension was the most common comorbidity, observed in 56.45% of the participants. 72.26% of the present study participants had been asymptomatic, while 13.23% had a fever as their symptom of COVID-19. COVID-19 test was done on 81 patients, among whom 64 had tested positive. Among the total 310 participants, 29.03% had not received any vaccinations, while 14.19% had received only 1st dose of vaccination, 47.2% had received up to their 2nd dose, and 9.35% had received their booster dose. Conclusions: The present study observed a low incidence rate of COVID-19 positive patients among those affected by chronic kidney disease. However, the study also observed a significant positive relation between COVID-19 positive patients and the need for additional medical support, leading to the conclusion that COVID-19 can significantly affect the severity of CKD.